Cubic B-spline method for the solution of an inverse parabolic system. Issue 3 (17th February 2018) - Foadian, Saedeh; Pourgholi, Reza; Hashem Tabasi, S.
Abstract: In this paper, a numerical method is proposed for the numerical solution of a linear system with suitable initial and boundary conditions using the cubic B-spline collocation scheme to determine the unknown boundary condition. We apply the cubic B-spline for the spatial variable and the derivatives which, generate an ill-posed linear system of equations. In this regard, to overcome, to this drawback, we employ the Tikhonov regularization method for solving the resultant linear system. It is proved that the proposed method has the order of convergence . Also, the conditional stability using the Von-Neumann method is established under suitable assumptions. Finally, some numerical results are reported to show the efficiency and robustness of the proposed approach for solving the inverse problems.